Community characteristics of autotrophic CO2-fixing bacteria in karst wetland groundwaters with different nitrogen levels - Wang, Xiayu; Li, Wei; Cheng, Aoqi; Shen, Taiming; Xiao, Yutian; Zhu, Min; Pan, Xiaodong; Yu, Longjiang (Frontiers in Microbiology, 2022)
Karst wetlands are important in the global carbon and nitrogen cycles as well as in security of water resources. Huixian wetland (Guilin) is the largest natural karst wetland in China. In recent years, groundwater nitrogen pollution has increasingly affected the wetland ecosystem integrity due to anthropogenic activities. In this study, it was hypothesized that autotrophic microbial diversity is impacted with the advent of pollution, adversely affecting autotrophs in the carbon and nitrogen cycles. Autotrophic microbes have important roles in abating groundwater nitrogen pollution. Thus, it is of great significance to study the characteristics of autotrophic bacterial communities and their responses to environmental parameters in nitrogen-polluted karst groundwaters. The abundances of the Calvin–Benson cycle functional genes cbbL and cbbM as well as the autotrophic CO2-fixing bacterial communities were characterized in the karst groundwater samples with different levels of nitrogen pollution. The cbbM gene was generally more abundant than the cbbL gene in the groundwater samples. The cbbL gene abundance was significantly positively correlated with dissolved inorganic nitrogen (DIN) concentration (P < 0.01). In the autotrophic CO2-fixing bacterial communities, Alphaproteobacteria, Betaproteobacteria, and Gammaproteobacteria of the phylum Proteobacteria were predominant. At the genus level, Rubrivivax and Methylibium were the dominant cbbL gene containing genera, while Halothiobacillus and Endothiovibrio were the dominant genera for the cbbM gene. The abundance of autotrophic CO2-fixing bacterial communities increased but their diversity decreased with the inflow of nitrogen into the karst groundwater system. The community structure of autotrophic CO2-fixing bacteria in the groundwaters was also significantly affected by environmental factors such as the carbonic anhydrase (CA) activity, dissolved inorganic carbon (DIC) concentration, temperature, and oxidation-reduction potential (ORP). Nitrogen inflow significantly changed the characteristics of autotrophic CO2-fixing bacterial communities in the karst groundwaters. Some key genera such as Nitrosospira and Thiobacillus were clearly abundant in the karst groundwaters with high nitrogen levels. Their respective roles in nitrification and denitrification impact nitrogen removal in this ecosystem. The findings in this study provide an important reference for biological abatement of nitrogen pollution in the karst groundwater system.